Applications of Crystal Engineering in Drug Delivery - Al-Obaidi, Hisham (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Crystal engineering is a broad area of research that includes crystal habit modification, polymorphism, solid dispersions, and salt formation. This reprint covers state-of-the-art applications of crystal engineering and includes a combination of research and review articles, with special emphasis on novel drug delivery and targeting applications.